2006
DOI: 10.1542/peds.2005-2704
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Child Development at Sick-Child Visits: A Controlled Trial

Abstract: The Care for Development Intervention is an effective method of supporting caregivers' efforts to provide a more stimulating environment for their children and can be used by health care professionals during visits for acute minor illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(108 citation statements)
references
References 35 publications
1
101
0
6
Order By: Relevance
“…25 Other studies have also demonstrated the effectiveness of child development training processes that are aimed at medical students and primary healthcare professionals, in institutional programs that ensure not only health promotion and disability prevention but also care for children who have been identified as presenting a problem in their development. 26,27 Parents' opinions regarding their children's development have been recognized by many researchers as having high sensitivity and specificity for detecting possible disorders. [28][29][30][31] However, primary care professionals do not always fully appreci- ing courses, and it also needs to be adopted by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…25 Other studies have also demonstrated the effectiveness of child development training processes that are aimed at medical students and primary healthcare professionals, in institutional programs that ensure not only health promotion and disability prevention but also care for children who have been identified as presenting a problem in their development. 26,27 Parents' opinions regarding their children's development have been recognized by many researchers as having high sensitivity and specificity for detecting possible disorders. [28][29][30][31] However, primary care professionals do not always fully appreci- ing courses, and it also needs to be adopted by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 For example, following training on communication techniques to promote care for child development, pediatricians in Turkey improved counseling skills, such as asking caregivers questions and encouraging the caregiver to share experiences about play or stimulation. 18 It is worth noting that a critical challenge for delivering ECD services through the healthcare system is the fact that the health system is steeped in a traditional medical model, and that communities have come to expect physical remedies for all ills (e.g., pills, injections, and supplements) from health professionals. 19 Behavioral-change interventions such as promotion of care for infant and young-child feeding require a shift in the paradigm of the health workers and counseling in a way that the family moves away from the expectations for the medical model of care.…”
Section: Building Capacity At the Level Of Health Service Providersmentioning
confidence: 99%
“…The literature evidence in support of the ECD implementation of UNICEF's Care for Child Development module is established and ideal for group learning settings [15,[20][21][22]29]. The complete Care for Child Development module contains activities and learning modules described in the Care for Child Development: Facilitator Notes [30].…”
Section: Educational Interventionmentioning
confidence: 99%
“…Incorporating early child development activities into the health system provides opportunities for reaching vulnerable children that manifest behavior and social issues, poor adaptation, and lower cognitive and educational attainment [9,14,15]. An integration of ECD into established maternal and child-health visits ensure cost-effectiveness and time efficiency for both caregiver and health-worker [2,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation